Anti-neuroinflammatory effects of citreohybridonol involving TLR4-MyD88-mediated inhibition of NF-кB and MAPK signaling pathways in lipopolysaccharide-stimulated BV2 cells. (May 2016) - Cho, Kwang-Ho; Kim, Dong-Cheol; Yoon, Chi–Su; Ko, Won Min; Lee, Seung Jun; Sohn, Jae Hak; Jang, Jae-Hyuk; Ahn, Jong Seog; Kim, Youn-Chul; Oh, Hyuncheol
Abstract: In the course of searching for anti-neuroinflammatory metabolites from marine fungi, citreohybridonol was isolated from marine-derived fungal strain Toxicocladosporium sp. SF-5699. Citreohybridonol inhibited production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) in BV2 cells stimulated by lipopolysaccharide (LPS). Citreohybridonol also suppressed the expression of inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), and other pro-inflammatory cytokines including interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the LPS-stimulated cells. In the further study, citreohybridonol disturbed nuclear translocation of nuclear factor-kappa B (NF-κB) in LPS-stimulated BV2 cells by inhibiting the phosphorylation of the inhibitor kappa B-α (IκB-α). Citreohybridonol also had inhibitory effect on the LPS-stimulated phosphorylation of p38 mitogen-activated protein kinase (MAPK). Finally, citreohybridonol suppressed the protein expression of Toll-like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88) in LPS-induced BV2 cells. These results suggest that citreohybridonol has anti-neuroinflammatory effect in LPS-stimulated BV2 cells by modulating TLR4-mediated several inflammatory pathways such as NF-κB and p38 MAPK pathways. Highlights: Citreohybridonol was isolated from the marine-derived fungal strain Toxicocladosporium sp. SF-5699. Citreohybridonol suppressed NF-кB and MAPK-related neuroinflammatory enzymes and cytokines in LPS-stimulated BV2 cells. Citreohybridonol inhibited several TLR4-mediated inflammatory pathways.